KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMPN 02 MERAL - Erika Yulidasari Putri; Suripah Suripah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to describe the mathematical creative thinking skills of SMPN 2 Meral students on the material of flat side space. This type of research is descriptive with a quantitative approach. The data collection technique used is in the form of a written test in the form of questions about the material for building flat sides, documentation, and interviews. This study uses qualitative descriptive data analysis techniques, namely: (1) data reduction; (2) triangulation of data; (3) analyzing the results of written tests and interviews; (4) Drawing conclusions. This research focuses on 4 aspects, namely: (1) Fluency; (2) Flexibility; (3) Elaboration (elaboration); and (4) Authenticity (originality). The results of this study indicate that students' creativity in answering fluency indicator questions is 66.6% which is included in the creative category, 83.3% flexibility indicator questions which are very creative, and elaboration indicator questions are 41.6 % which is categorized as quite creative, 79.1% of originality indicators are included in the creative category, and the average percentage of creative thinking for class IX students at SMPN 2 Meral is 67.65% in the creative category.